2019
DOI: 10.5858/arpa.2019-0472-ra
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Neoplasms With Acinar Differentiation: A Review of Pathologic and Molecular Features

Abstract: Context.— Pancreatic acinar lesions encompass a broad spectrum of malignant tumors and benign reactive processes affecting both adults and children, with clinical, pathologic, and molecular features that are distinct from more common ductal neoplasms. Accurate morphologic diagnosis and molecular assessment of these uncommon neoplasms is critical for effective patient care. Objective.— To review the clinical, pathologic, and molecular features of pancreatic neoplasms with acinar differentiation, the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 57 publications
(67 reference statements)
1
53
0
Order By: Relevance
“…Pathologically, these tumors are considered as part of the "pancreatic carcinomas with acinar differentiation, " with acinar cell carcinomas and carcinomas of mixed differentiation (11). Squamoid nests are the key morphologic feature of pancreatoblastoma; a neuroendocrine component is frequently found (12). On IHC, a very distinctive feature is the abnormal nuclear and cytoplasmic localization of β-catenin, usually restricted to the squamoid nests (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathologically, these tumors are considered as part of the "pancreatic carcinomas with acinar differentiation, " with acinar cell carcinomas and carcinomas of mixed differentiation (11). Squamoid nests are the key morphologic feature of pancreatoblastoma; a neuroendocrine component is frequently found (12). On IHC, a very distinctive feature is the abnormal nuclear and cytoplasmic localization of β-catenin, usually restricted to the squamoid nests (12).…”
Section: Discussionmentioning
confidence: 99%
“…Squamoid nests are the key morphologic feature of pancreatoblastoma; a neuroendocrine component is frequently found (12). On IHC, a very distinctive feature is the abnormal nuclear and cytoplasmic localization of β-catenin, usually restricted to the squamoid nests (12).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a genome-wide analysis identified no recurrent point mutations in ACCs[ 124 ]. Microsatellite instability was detected in a fraction of ACC ranging from 7% to 14% of cases[ 127 ]. ACC with MSI did not exhibit distinct morphological or clinical features[ 128 ].…”
Section: Other Pancreatic Tumorsmentioning
confidence: 99%
“…Although acinar cells represent over 80% of the pancreas, pancreatic acinar cell carcinoma (PACC) is rare, accounting for approximately 1% of primary pancreatic neoplasms [1]. Recent studies demonstrated that PACC was quite different from pancreatic ductal cell carcinoma (PDCC) in clinical, pathologic and molecular features and had a signi cantly better survival [2][3][4]. Therapeutic strategy of PACC should be distinguished [1,5,6].…”
Section: Introductionmentioning
confidence: 99%